Sudden death after a bite by a lowland swamp viper (Proatheris superciliaris) in Malawi: Dying of fright? - Beth A. Tippett Barr; Gary Brown; Mike Perry; Renee Ridzon; David A. Warrell (Toxicon, 2023)

Regional climate trend analyses for Aqua MODIS land surface temperatures - Abigail Marie Waring; Darren Ghent; Mike Perry; Jasdeep Singh Anand; Karen L Veal; John Remedios (International Journal of Remote Sensing, 2023)

Control history, longitude and multiple abiotic and biotic variables predict the abundances of invasive brushtail possums in New Zealand forests - David M. Forsyth; David S. L. Ramsey; Mike Perry; Meredith McKay; Elaine F. Wright (Biological Invasions, 2018)

Effects of Spatially Extensive Control of Invasive Rats on Abundance of Native Invertebrates in Mainland New Zealand Forests - WENDY A. RUSCOE; PETER J. SWEETAPPLE; MIKE PERRY; RICHARD P. DUNCAN (Conservation Biology, 2013)
Predation on native fauna by non‐native invasive mammals is widely documented, but effects of predation at the population level are rarely measured. Eradication of invasive mammals from islands has led to recovery of native biota, but the benefits of controlling invasive mammal populations in settings where eradication is not feasible are less understood. We used various combinations of aerially delivered toxic bait and control measures on the ground to reduce abundances of invasive rats (Rattus rattus) to low levels over large areas on mainland New Zealand and then monitored the abundance of invertebrates on replicated treatment sites to compare with abundances on similar nontreatment sites. We also assessed rat diet by examining stomach contents. Abundance of the rats’ most‐consumed invertebrate prey item, the large‐bodied Auckland tree weta (Hemideina thoracica), increased 3‐fold on treatment sites where we maintained rats at . Efectos del Control Extensivo Espacial de Ratas Invasoras sobre la Abundancia de Invertebrados Nativos en Bosques de Nueva Zelanda

Hydrogeology of Wadi Wurayah, United Arab Emirates, and its importance for biodiversity and local communities - Christophe Tourenq; Mike Brook; Sandra Knuteson; Maral Khaled Shuriqi; Moaz Sawaf; Lisa Perry (Hydrological Sciences Journal, 2011)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Strategies for selection marker-free swine transgenesis using the Sleeping Beauty transposon system - Daniel F. Carlson; John R. Garbe; Wenfang Tan; Mike J. Martin; John R. Dobrinsky; Perry B. Hackett; Karl J. Clark; Scott C. Fahrenkrug (Transgenic Research, 2011)

Electrophysiological Responses of Male Potato Cyst NematodesGlobodera rostochiensis and G. pallidato Some Chemicals - Ekaterini Riga; Roland N. Perry; John Barrett; Mike R. L. Johnston (Journal of Chemical Ecology, 1997)